Expanding the knowledge of Hyalella Smith, 1874 (Amphipoda: Hyalellidae) for southeast Brazil: two new troglophilic species from caves of the Atlantic Rainforest - Deotti, Carolina Mendes [UNESP]; Penoni, Ludmila Rocha; Bichuette, Maria Elina; Bueno, Alessandra Angélica de Pádua (FapUNIFESP (SciELO), 2025)
ABSTRACT The present work describes two new species of Hyalella Smith, 1874 from two different state parks in Southeastern Brazil. Both species were collected in well-preserved and conserved areas of the Atlantic Rainforest, the first from the Parque Estadual Intervales (PEI) and the other from the Parque Estadual Turístico do Alto Ribeira (PETAR). The two species are troglophilic, i.e., facultative cave-dwellers. They are found inside the caves but do not present any noticeable adaptation to life underground. Hyalella bocaina sp. nov. most distinguishable features include the palp of maxilla 1 reaching almost half the distance between base of the palp and base of setae on the outer plate, gnathopod 1 propodus inner face with serrate setae, peduncle of the pleopod covered with several setules, uropod 1 of the male without curved seta, and the uropod 3 shorter than the telson. Hyalella temimina sp. nov., although found exclusively inside of the Temimina II cave, does not present troglomorphisms, and its main characteristics are the relatively long palp of maxilla 1, the rich ornamentation of the telson, gnathopod 1 propodus inner face with pappose setae, uropod 1 of the male without curved seta, and the excavation of the apex of the ramus of uropod 3. Here we increase the number of Hyalella species known for Brazil from 42 to 44.